Crystallization Kinetics of an Equimolar Liquid Crystalline Mixture and Its Components - Aleksandra Deptuch; Anna Paliga; Anna Drzewicz; Marcin Piwowarczyk; Magdalena Urbańska; Ewa Juszyńska-Gałązka (Applied Sciences)
This new equimolar mixture comprises the liquid crystalline compounds MHPOBC and partially fluorinated 3F2HPhF6. The phase sequence of the mixture was determined by differential scanning calorimetry, polarizing optical microscopy, X-ray diffraction, and broadband dielectric spectroscopy. The enantiotropic smectic A*, C*, and CA* phases were observed for the mixture. Only partial crystallization of the mixture was observed during cooling at 2–40 K/min, and the remaining smectic CA* phase underwent vitrification. In contrast, the crystallization of the pure components was complete or almost complete for the same range of cooling rates. The kinetics of the non-isothermal and isothermal crystallization of the mixture and its pure components were investigated by differential scanning calorimetry. The non-isothermal data were analyzed by the isoconversional method, while the isothermal data were analyzed using the Avrami model. As is typical, the nucleation-controlled crystallization kinetics were observed.